(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
One of the gaps that exist in the historiography dealing with the history of the Indian people of Michoacan, is referred to the Otomi and Mazahua located on the eastern side of the state. In a way, the Tarascan or Purepecha strong presence that still ex- ists in many parts of the state, and the enormous task of evangelization of Vasco de Quiroga in that vast diocese, determined researchers to address these issues instead of other ethnic minorities. Based on the Franciscan chronicles, and geographic rela- tionships of the sixteenth century relied on unpublished documents from local and foreign files, as well as literature on the fifteenth, sixteenth and seventeenth centu- ries, this article reconstructs the history of Eastern Otomi and Mazahua Michoacan before the Conquest and after. The study highlights the arrival of the two groups to the “Michoaque” territory in the mid-fifteenth century and the role both played during the military conquest undertaken by the Spanish in 1522. It also examines the influence exerted upon them the Franciscan evangelization, the different pro- ductive activities in which they were involved and the strategies that they used to maintain control of their territory and defend their identity.